2021
DOI: 10.1111/pbi.13532
|View full text |Cite
|
Sign up to set email alerts
|

Large‐fragment insertion activates gene GaFZ (Ga08G0121) and is associated with the fuzz and trichome reduction in cotton (Gossypium arboreum)

Abstract: Summary Cotton seeds are typically covered by lint and fuzz fibres. Natural ‘fuzzless’ mutants are an ideal model system for identifying genes that regulate cell initiation and elongation. Here, using a genome‐wide association study (GWAS), we identified a ~ 6.2 kb insertion, larINDELFZ, located at the end of chromosome 8, composed of a ~ 5.0 kb repetitive sequence and a ~ 1.2 kb fragment translocated from chromosome 12 in fuzzless Gossypium arboreum. The presence of larINDELFZ was associated with a fuzzless s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 89 publications
1
14
0
Order By: Relevance
“…The GL2-interacting-repressors (GIRs) negatively regulate root hair development by interacting with GL2 and controlling the interaction network (Wu and Citovsky 2017a, b). Several recent studies indicated that GaFzl, which is annotated as GIR1 in diploid cotton, adversely affects fuzz development (Du et al 2018;Feng et al 2019;Liu et al 2020;Wang et al 2020c). However, the characteristics and underlying mechanisms of the GIRs functions and regulatory network in cotton remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The GL2-interacting-repressors (GIRs) negatively regulate root hair development by interacting with GL2 and controlling the interaction network (Wu and Citovsky 2017a, b). Several recent studies indicated that GaFzl, which is annotated as GIR1 in diploid cotton, adversely affects fuzz development (Du et al 2018;Feng et al 2019;Liu et al 2020;Wang et al 2020c). However, the characteristics and underlying mechanisms of the GIRs functions and regulatory network in cotton remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Cotton is cross-pollinated, and there were many genetic variations that existed among different cotton cultivars. Although gene sequences of GaFZ and its homologous gene of GhSRNF5/18 are highly conserved, there are divergences in their promoter regions (Feng et al, 2019 ; Wang et al, 2021 ), suggesting that their expression patterns may vary greatly among different cotton cultivars. Consequently, GhSRNF18 probably are involved in root development in some upland cotton cultivars, although the level of GhSRNF18 expression in roots of TM-1 was relatively low ( Figure 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…In Arabidopsis , GIR1 and GIR2 interact with GL2 and TPL proteins in the nucleus due to the BiFC assays (Wu and Citovsky, 2017a , b ). GhSRNF18 orthologous GaSRNF7 (GaFZ) protein was observed predominantly in the membrane and nucleus (Wang et al, 2021 ). The results of subcellular localization assays in Arabidopsis protoplast showed GhSRNF18 distributed in the nucleus ( Figure 9 ), which implies that GhSRNF18 may control the expression level of several PR-related genes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations